The Antioxidant Peroxiredoxin 6 (Prdx6) Exhibits Different Profiles in the Livers of Seawater- and Fresh Water-Acclimated Milkfish, Chanos chanos, upon Hypothermal Challenge - Chang, Chia-Hao; Lo, Wan-Yu; Lee, Tsung-Han (Frontiers in Physiology, 2016)
A tropical species, the euryhaline milkfish (Chanos chanos), is a crucial economic species in Southeast Asia and is intolerant of water temperature below 12°C. Large numbers of milkfish die during cold periods in winter. Hypothermal environments usually increase oxidative stress in teleosts, and the liver is the major organ for anti-oxidative responses in the body. Peroxiredoxin-6 (Prdx6) in mammals is a multi-functional enzyme and acts as both glutathione peroxidase, phospholipase A2 and acyl-transferase for maintenance of redox status and prevention of cell membrane peroxidation. Prdx6 can protect cells from oxidant-induced membrane damage by translocating the Prdx6 protein from the cytosol to the membrane. Upon cold stress, Ccprdx6 transcript levels were up-regulated after 24 h and 96 h in livers of fresh water (FW)- and seawater (SW)-acclimated milkfish, respectively. In the hypothermal FW group, the Prdx6 protein was up-regulated in the cytosol of hepatocytes with a similar role as glutathione peroxidase to reduce oxidative stress upon hypothermal challenge. Conversely, in hypothermal SW milkfish, total Prdx6 protein was down-regulated. However, cytosolic Prdx6 protein was translocated to the membrane, using the ability of phospholipase A2 to stabilize the membrane redox state. Moreover, H2O2 content was increased in FW-acclimated milkfish livers upon hypothermal challenge. Ex vivo H2O2 treatment of milkfish livers also induced Ccprdx6 transcriptional expression, which provided more evidence of the antioxidant role of milkfish Prdx6. Taken together, upon hypothermal challenge, greater oxidative stress in livers of FW-acclimated milkfish rather than SW-acclimated individuals led to different profiles of hepatic CcPrdx6 expression between the FW and SW group. The results indicated that CcPrdx6 played the role of antioxidant with different mechanisms, i.e., binding to reactive oxygen species and stabilizing membrane fluidity, in livers of hypothermal FW and SW milkfish, respectively.